Measuring Information Development In The New Millennium - Ramasamy, Ramachandran (2008)
This thesis has adopted a socio-technology approach for measuring the progress made in the information age. Viewing from public policy perspectives the discussion is apportioned under two broad areas, namely info-age conceptual framework and measurement and computational framework. The research is premised upon the notion that the new age technologies, in particular the Internet being pervasive and ubiquitous is bringing about dramatic and unprecedented changes in the ways individuals and institutions work, learn, play, entertain, network, interact and perform transactions and delivery.